The Associated Factors with Breastfeeding Self-Efficacy Among Breastfeeding Women in Kalimantan Utara - Widiya Rolantika; Annisa Nurrachmawati; Ike Anggraeni (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2024)
Exclusive breastfeeding is important for the quality of children's health. Nevertheless, the proportion of exclusive breastfeeding at the Malinau City Health Center stands at a mere 45.6 percent, falling short of the 50 percent benchmark set by the World Health Organization (WHO). nursing self-efficacy is a significant element that affects nursing behavior. This study aims to determine the factors related to breastfeeding self-efficacy. This study was cross-sectional, with a sample of 147 mothers obtained by purposive sampling. Breastfeeding Self Efficacy (BSE) is measured using the Breastfeeding Self Efficacy Short-Form. Data was analyzed using the Chi-Square test. The results showed that there was a significant relationship between breastfeeding problems (p-value equals 0.001), family support (p-value equals 0.001), and health worker support (p-value equals 0.001) with breastfeeding self-efficacy. It is concluded that breastfeeding problems, family support, and health worker support were factors related to breastfeeding self-efficacy in breastfeeding mothers. Therefore, health workers and families are expected to support mothers when they have breastfeeding problems